Study on the mechanical properties of limestone materials with different moisture contents under cyclic loading and unloading - Tingkai Hou; Zonghong Zhou; Jing Zhang; Yonggang Zhang (Frontiers in Materials)
IntroductionIn order to reduce the impact of secondary disasters caused by the instability of rock and soil mass (RSM) during engineering construction on the environment, and to achieve safe and efficient engineering construction. Therefore, investigating the mechanical properties (M.P.), energy evolution laws, and damage characteristics of limestone with different water saturation (w) under cyclic loading-unloading (CLU) conditions is of significant engineering significance.MethodsThis study conducted uniaxial compression (UC) and cyclic loading-unloading tests on limestone samples with different w values (i.e., 0%, 25%, 50%, 75%, 100%) to elucidate their mechanical properties and energy dissipation. The influence of w on the degradation of limestone was examined based on damage variables.ResultsThe results indicated that (1) as w increases, both the compressive strength (fc) and elastic modulus (E) of the samples gradually decrease, while the peak axial strain gradually increases. When the w exceeded 0.4%, the failure characteristics transitioned from brittleness to ductility. (2) For limestone samples with the same w, the fc and E under CLU conditions were greater than those under uniaxial compression conditions, while the peak axial strain was smaller than that under UC conditions. Analysis using the DRA method confirmed that w did not significantly affect the deformation memory effect of limestone. (3) As the axial strain and number of cycles (N) increased, both the input energy and dissipated energy gradually increased, while the elastic energy initially increased before rapidly declining. The proportion of elastic energy first increased and then decreased, while the proportion of dissipated energy first increased, then decreased, and finally suddenly increased. Compared with UC, CLU significantly enhanced the rock’s capacity to store elastic energy. (4) For the same N, limestone with higher w exhibited greater damage than that with lower w. Moreover, samples with high w always failed earlier than those with low w under both the UC and CLU conditions.DiscussionThe research results provide a theoretical basis for understanding the dynamic response behavior and stability analysis of limestone slopes under disturbance and rainfall effects.